Effects of Aggregate Types on the Stress-Strain Behavior of Fiber Reinforced Polymer (FRP)-Confined Lightweight Concrete - Pengda Li (Sensors, 2018)
The realization of reducing concrete self-weight is mainly to replace ordinary aggregates with lightweight aggregates; such replacement usually comes with some intrinsic disadvantages in concrete, such as high brittleness and lower mechanical properties. However, these shortages can be effectively remedied by external confinement such as fiber reinforced polymer (FRP) jacketing. To accurately predict the stress-strain behavior of lightweight concrete with lateral confinement, it is necessary to properly understand the coupling effects that are caused by diverse aggregates types and confinement level. In this study, FRP-confined lightweight concrete cylinder with varying aggregate types were tested under axial compression. Strain gauges and linear variable displacement transducers were used for monitoring the lateral and axial deformation of specimens during the tests. By sensing the strain and deformation data for the specimens under the tri-axial loads, the results showed that the lateral to axial strain relation is highly related to the aggregate types and confinement level. In addition, when compared with FRP-confined normal weight aggregate concrete, the efficiency of FRP confinement for lightweight concrete is gradually reduced with the increase of external pressure. Replace ordinary fine aggregate by its lightweight counterparts can be significantly improved the deformation capacity of FRP-confined lightweight concrete, meanwhile does not lead to the reduction of compressive strength. Plus, this paper modified a well-established stress-strain model for an FRP-confined lightweight concrete column, involving the effect of aggregate types. More accurate expressions pertaining to the deformation capacity and the stress-strain relation were proposed with reasonable accuracy.